1981
DOI: 10.1007/bf02374083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and zinc on the yield of submerged rice and uptake of N and Zn on unlimed and limed soils

Abstract: SUMMARYThe effect of N and Zn on the yield of submerged rice and uptake of N and Zn was studied on limed and unlimed soils in greenhouse. Nitrogen was applied at the rate of 0, 80 and 160 ppm through urea, ammonium sulphate and ammonium nitrate, Zn at 0 and 10 ppm in limed (4~ CaCO3) and unlimed soils. Liming (4~ CaCO3) decreased dry matter yield of rice at tillering, heading and straw and grain at maturity significantly against unlimed treatments. Ammonium sulphate gave highest yield with all applied doses fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Non-judicious use of nitrogen fertilizer could further aggravate Zn deficiency in alkaline soils and suppress paddy growth and yield (Rashid, 1996). Nitrogen fertilization is found to enhance zinc contents of flooded rice, where urea performed better than NH4NO3 in increasing Zn contents (Chaudhry et al, 1977;Singh and Singh, 1981). They observed that higher Zn contents in plant tissues by nitrogen application were due to better growth, increased Zn solubility and increased root efficiency for Zn uptake.…”
Section: Paddy Yield Componentsmentioning
confidence: 99%
“…Non-judicious use of nitrogen fertilizer could further aggravate Zn deficiency in alkaline soils and suppress paddy growth and yield (Rashid, 1996). Nitrogen fertilization is found to enhance zinc contents of flooded rice, where urea performed better than NH4NO3 in increasing Zn contents (Chaudhry et al, 1977;Singh and Singh, 1981). They observed that higher Zn contents in plant tissues by nitrogen application were due to better growth, increased Zn solubility and increased root efficiency for Zn uptake.…”
Section: Paddy Yield Componentsmentioning
confidence: 99%